"Mission and Duties of Young Women": Charles White and the Promotion of Catholic Domesticity in Antebellum Baltimore - Mannard, Joseph (American catholic studies, 2010)
Born in Baltimore in 1807 and ordained in Paris in 1830, the Reverend Charles Ignatius White was a leading member of the Catholic press in antebellum America. White served as founder/editor of several important periodicals, including a weekly newspaper and a monthly literary journal. Neglected by scholars, however, has been White's significant contribution to advancing a Catholic version of the ideology of domesticity. Most noteworthy in this regard was his book Mission and Duties of Young Women (1858), a translation of a popular advice book by the French author Charles Sainte-Foi. A review of White's literary output – as editor, writer, biographer, and translator – complicates and qualifies our understanding of the temporal, geographical, ethnic, and class origins of American Catholic domesticity, at least for antebellum Baltimore. Led by its native-born gentry of largely English stock, the Maryland Catholic community had traditionally accommodated itself more easily to mainstream American cultural values than did the predominantly working-class, immigrant Catholics in the urban North. Through his writings promoting a Catholic version of true womanhood, Charles White served as a mid-century bridge between an older culture, dominated by a native-born, Anglo-Catholic elite, and that of an emerging immigrant church in the nation's oldest archdiocese.